2021
DOI: 10.1371/journal.pone.0248730
|View full text |Cite
|
Sign up to set email alerts
|

Variability in digestive and respiratory tract Ace2 expression is associated with the microbiome

Abstract: COVID-19 (coronavirus disease 2019) patients exhibiting gastrointestinal symptoms are reported to have worse prognosis. Ace2 (angiotensin-converting enzyme 2), the gene encoding the host protein to which SARS-CoV-2 spike proteins bind, is expressed in the gut and therefore may be a target for preventing or reducing severity of COVID-19. Here we test the hypothesis that Ace2 expression in the gastrointestinal and respiratory tracts is modulated by the microbiome. We used quantitative PCR to profile Ace2 express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 20 publications
2
28
0
1
Order By: Relevance
“…Nevertheless, the ACE2-MAS axis constitutes a promising therapeutic target and represents a potential factor that underlies microbiome-related effects. It has been shown that modulation of bacterial composition may impact the amount of ACE2 in the intestine ( 121 123 ). In line with this, it has been shown that ACE2 gene expression in tissues from colorectal cancers was positively correlated with the abundance of specific bacterial taxa, most prominently Chlamydia ( 124 ).…”
Section: Ras and Gut Microbiota In Health And Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, the ACE2-MAS axis constitutes a promising therapeutic target and represents a potential factor that underlies microbiome-related effects. It has been shown that modulation of bacterial composition may impact the amount of ACE2 in the intestine ( 121 123 ). In line with this, it has been shown that ACE2 gene expression in tissues from colorectal cancers was positively correlated with the abundance of specific bacterial taxa, most prominently Chlamydia ( 124 ).…”
Section: Ras and Gut Microbiota In Health And Diseasementioning
confidence: 99%
“…The latest study on mice supports these results as ACE2 levels in intestines were significantly higher in germ-free animals than in conventional mice. The germ-free phenotype was partially recapitulated by antibiotic treatment ( 123 ).…”
Section: Ras and Gut Microbiota In Health And Diseasementioning
confidence: 99%
“…Additionally, some studies have shown a relationship between the composition of the gut and respiratory microbiota and disease severity [12]. This relationship appears to be mainly based on the capacity of the microbiota to modulate the immune response [13,14], through modification of the gut-lung axis [12,15,16], and to alter the expression of angiotensin-converting enzyme 2 (ACE2) receptors, which are used by SARS-CoV-2 to enter host cells [17,18].…”
Section: Introductionmentioning
confidence: 99%
“… 289 , 290 Several studies have found a reduction of ACE2 expression in the gastrointestinal tract in SARS-CoV. 291 , 292 As a consequence, the decrease in ACE2 may account for the decrease in tryptophan absorption in the gastrointestinal tract. This may account for the gastrointestinal symptoms caused by SARS-CoV-2, such as diarrhea, and may be a potential regulatory mechanism of the gut microbiome.…”
Section: New Biomarkers-based Laboratory Findings For Covid-19 Detectionmentioning
confidence: 99%